THE ROLE OF MICROBIAL COMMUNITIES IN ECOSYSTEM RESILIENCE: INSIGHTS FROM SOIL AND WATER ECOSYSTEMS - Lucia Moretti (Modern American Journals, 2025)
Microbial communities play a critical role in maintaining ecosystem stability and resilience, particularly in soil and water ecosystems. These microorganisms, although often invisible to the naked eye, regulate essential processes such as nutrient cycling, organic matter decomposition, and disease suppression. Their interactions with the environment and other organisms are fundamental to ecosystem health, especially in the face of environmental stresses induced by climate change and human activities. This paper explores the role of microbial communities in enhancing ecosystem resilience, focusing on their functions in soil health, water quality, and biodiversity preservation. We highlight recent research on the resilience of microbial communities in the face of environmental disturbances and the implications for ecosystem services. The study emphasizes how managing microbial diversity can be integral to sustainable land and water management practices, which are key to mitigating the negative effects of global environmental change.
Keywords: Microbial Communities, Ecosystem Resilience, Soil Ecosystems, Water Ecosystems, Climate Change, Biodiversity, Nutrient Cycling, Water Quality, Ecosystem Services, Environmental Stress